1975
DOI: 10.1037/0012-1649.11.5.651
|View full text |Cite
|
Sign up to set email alerts
|

Information processing in low- and high-test-anxious children as a function of grade level and verbal labeling.

Abstract: Recently Sarason (1972) and Wine (1971) discussed the negative effects of test anxiety within an attentional framework. Wine suggested that in evaluative situations high-testanxious (HTA) persons divide their attention between task-relevant and task-irrelevant information, for example, self-stimuli such as worry. Sarason focused on HTA subjects' attention to relevant and irrelevant situational cues. In the present research several implications of these attentional theories of test anxiety were investigated.Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…In the studies by Dusek et al (1975Dusek et al ( , 1976, the secondary task stimuli (drawings of household objects) were comparable in salience to the primary task stimuli (drawings of animals) and were presented together. In both studies, participants high in test anxiety had significantly better recall of the secondary task stimuli than those low in test anxiety, with the opposite being the case for recall of the primary task stimuli.…”
Section: Hypothesis 3: Anxiety Impairs Attentional Control By Increasmentioning
confidence: 99%
“…In the studies by Dusek et al (1975Dusek et al ( , 1976, the secondary task stimuli (drawings of household objects) were comparable in salience to the primary task stimuli (drawings of animals) and were presented together. In both studies, participants high in test anxiety had significantly better recall of the secondary task stimuli than those low in test anxiety, with the opposite being the case for recall of the primary task stimuli.…”
Section: Hypothesis 3: Anxiety Impairs Attentional Control By Increasmentioning
confidence: 99%
“…High-anxious children also performed less well, and their difficulty staying on task was probably an important reason why. Dusek, Kermis, and Mergler (1975) and Dusek,Mergler,and Kermis (1 976) found that high-anxious children attended less well to the central stimuli in a positionlearning task and thus performed more poorly than low-anxious children. Instead of focusing on the central stimuli, highanxious children were more distracted by the nonessential (or incidental) stimuli in the task.…”
Section: The Problem Of Anxiety Anxiety: Its Nature and Importancementioning
confidence: 99%
“…Sarason (1972) suggested that a reassuring, task-oriented atmosphere reduced the performance decrements suffered by HA adults. Dusek, Kermis, and Mergler (1975) found that the performance decrements of HA children only appeared when the task was presented as a test and not when the task was presented as a game. These data suggest that the test-taking environment affects the extent to which test anxiety impairs performance.…”
mentioning
confidence: 94%